2011
DOI: 10.1371/journal.pone.0016458
|View full text |Cite
|
Sign up to set email alerts
|

Primary Human mDC1, mDC2, and pDC Dendritic Cells Are Differentially Infected and Activated by Respiratory Syncytial Virus

Abstract: Respiratory syncytial virus (RSV) causes recurrent infections throughout life. Vaccine development may depend upon understanding the molecular basis for induction of ineffective immunity. Because dendritic cells (DCs) are critically involved in early responses to infection, their interaction with RSV may determine the immunological outcome of RSV infection. Therefore, we investigated the ability of RSV to infect and activate primary mDCs and pDCs using recombinant RSV expressing green fluorescent protein (GFP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 79 publications
(96 reference statements)
7
59
1
Order By: Relevance
“…4 and 5). Similar to our findings, previous studies showed the ability of RSV to induce production of these cytokines in isolated human pDCs and mDCs (73,74). However, our data show that these RSVinduced responses are impaired by the CX3C motif.…”
Section: Discussionsupporting
confidence: 92%
“…4 and 5). Similar to our findings, previous studies showed the ability of RSV to induce production of these cytokines in isolated human pDCs and mDCs (73,74). However, our data show that these RSVinduced responses are impaired by the CX3C motif.…”
Section: Discussionsupporting
confidence: 92%
“…The ability of clinical isolates of RSV (and metapneumovirus (MPV)) to attenuate TLR7/TLR9-induced IFN-I responses in pDCs has been consistently shown in human and murine models [104][105][106]. The infection of pDCs by RSV was implied when cell surface expression of the viral F protein was observed, which was later confirmed using green fluorescent protein-labelled RSV; although the fraction of infected pDCs was extremely low [103,107].…”
Section: Regulation Of Tlr7-mediated Responsesmentioning
confidence: 96%
“…In particular, several laboratories have demonstrated that type I IFNs (mainly IFN-␣ and IFN-␤) and their major producers, plasmacytoid dendritic cells (pDCs), are important in protection from RSV disease. It has been reported that RSV stimulates pDCs isolated from human peripheral blood mononuclear cells (13,14) or murine bone marrow-derived pDCs (15,16) to produce type I IFNs ex vivo. Furthermore, several publications have demonstrated that RSV infection of adult mice induces pulmonary type I IFNs in vivo (17,18) and that intranasal administration of recombinant IFN-␣ significantly reduces the lung viral load, inflammation, weight loss, and clinical illness scores of RSVinfected adult mice (19).…”
mentioning
confidence: 99%